Neuropeptides of root-knot nematodes: functional significance in parasite locomotions (short review) - T. A. Milyutina; Zh. V. Udalova (Российский паразитологический журнал, 2023)
The purpose of the research is to analyze the literature devoted to the study of the physiological role and functional significance of biologically active substances: FMRFamide-like neuropeptides in the locomotion of root-knot nematodes Meloidogyne incognita, M. minor, M. hapla and M. graminicola using immunological, phylogenetic, molecular and bioinformatic research methods.Results and discussion. The present work shows the importance of endogenous FMRFamide-like neuropeptides (FLPs) in such behavioral reactions of plant nematodes as locomotion, which ensures the vital activity of plant parasites; the functional significance of flp genes in the neurobiology of root-knot nematodes is discussed. It was especially noted that the main physiological and functional characteristics of endogenous FLP in root-knot nematodes were obtained as a result of studies of the functional role of the flp genes encoding these neuropeptides. In the nematodes M. incognita and M. graminicola, components of the peptidergic nervous system were identified in the nervous structures: FMRFamide-like positive immunoreactivity, FLP, flp genes encoding neuropeptides, and G-protein-coupled receptors (GPCR) activated by these neuropeptides. It was shown that the main functional characteristics of endogenous FLPs in nematodes were obtained using one of the methods of reverse genetics, i.e., flp genes knockdown in shadow by means of RNA-interference. It has been established that FLP cause two types of physiological effects on the somatic muscles of root-knot nematodes – stimulation of the locomotor activity of the muscles and its inhibition. In most works, the data obtained on the physiological effects of neuropeptides on the locomotor activity of phytonematodes are considered with a view to their possible use in the development of new targeted anthelmintic drugs.